Prognostic significance of preinjury anticoagulation in patients with traumatic brain injury: A systematic review and meta-analysis. Issue 1 (January 2021) - Lim, Xin Tian; Ang, Eshen; Lee, Zong Xuan; Hajibandeh, Shahin; Hajibandeh, Shahab
Abstract : BACKGROUND: Traumatic brain injury (TBI) is a leading cause of injury-related deaths and neurological disability globally. Considering the widespread anticoagulant use among the aging population, we aimed to perform a systematic review and meta-analysis to evaluate the prognostic significance of preinjury anticoagulation in TBI patients. METHODS: This systematic review was conducted according to a predefined protocol (International Prospective Register of Systematic Reviews CRD42020192323). In compliance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses and Meta-Analysis of Observational Studies in Epidemiology standards, a structured electronic database search was undertaken to identify all observational studies comparing preinjury anticoagulation with no preinjury anticoagulation in TBI patients. The primary outcome measure was overall mortality. The secondary outcome measures comprised in-hospital mortality, length of hospital stay, length of intensive care unit stay, need for neurosurgical procedure, and number of patients discharged home. All outcome data were analyzed using random effects modeling. RESULTS: Twelve comparative studies enrolling a total of 4, 417 patients were included. Preinjury anticoagulation was associated with higher risk of overall mortality (odds ratio [OR], 2.39; 95% confidence interval [CI], 1.63–3.50, p < 0.00001), in-hospital mortality (OR, 2.47; 95% CI, 1.56–3.93, p = 0.0001), and longer length of intensive care unit stay (mean difference, 1.06; 95% CI, 0.54–1.57; p < 0.0001) compared with no preinjury anticoagulation. No statistical difference was observed in length of hospital stay (mean difference, −2.15; 95% CI, −5.36 to 1.05, p = 0.19), need for neurosurgical procedure (OR, 1.30; 95% CI, 0.70–2.44; p = 0.41), and discharged home (OR, 0.76; 95% CI, 0.55–1.04; p = 0.09) between the two groups. CONCLUSION: Preinjury anticoagulation is a powerful prognosticator of mortality in TBI patients. This highlights the need for dedicated triage and trauma team activation protocols considering earlier intervention and more aggressive imaging in all anticoagulated patients. Future studies should focus on strategies that can potentially reduce the risk of mortality in this population. The prognostic significance of direct oral anticoagulants versus warfarin remains unanswered. LEVEL OF EVIDENCE: Systematic review and meta-analysis of observational studies, level III. Abstract : Supplemental digital content is available in the text.